Entrepreneurship in Sport: Sport in Business, Using Professional Football as an Example - Kowalski , Wojciech Szymon (Studia Historiae Oeconomicae, 2022)
The issue of entrepreneurship in sports joins the more general trend of catching up with the long Renaissance period of “reflecting” on the character of the professional sportsman (athlete), so peculiarly overlooked, and one of the main protagonists of the culture of antiquity, alongside the artist or philosopher. The author of the article adopts the convention of the ‘corporate athlete’, for which he sees a contemporary exemplification in football, the most popular sport. The examples cited from the economic history of football, preceded by an outline of the basic categories of entrepreneurship, are an attempt to show the essence of an economic, two-way view of these issues. The description of the institutionalisation of analytics and football’s ‘information bank’, highlights the effectiveness of an interdisciplinary approach to entrepreneurship in sport. In contrast, the characterisation of the re-engineering carried out at FC Barcelona is a case of an approach that treats sport as a natural economic environment. Providing a wholesome, inspirational building block, grounding some elements of management and entrepreneurial.